Arterial Complications Following Varicose Surgery - علي, سليمان (Latakia University Journal -Medical Sciences Series, 2020)
Varicose veins are a benign disease. Their surgical treatment, like other surgeries, can be a serious risk, which may be caused by the attending physician or the injured patient. In this research we have studied arterial complications of varicose surgery and the causes of their occurrence and the degree of seriousness and the most important preventive methods to avoid their occurrence and worsening sequels. We also mentioned several international studies concerned with this topic and classified the mixes and methods of management and the risks of ignoring them. This research confirms that the arterial complications of varicose surgery are rare, but they are present, and that the accuracy of surgical technique and follow-up after surgery reduces the risk of complications that can occur.